Implementasi Pembiayaan Modal Kerja dengan Menggunakan Akad Mudharabah pada Bank Syariah Indonesia (BSI) KC Meulaboh Imam Bonjol - Lili Affrida; Linda Rahmazaniati (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to find out that BSI KC Meulaboh Imam Bonjol has implemented the rules according to the Fatwa of the Sharia Council to convince the surrounding community that Bank Syariah Indonesia has implemented according to sharia. The distribution of Mudharabah financing provides services to those in need to help improve the economic situation of the community. Mudharabah financing provided by BSI KC. Meulaboh is very much needed by the community for working capital for trading businesses and plantations. The method used in the researcher is a descriptive method with a qualitative approach. The population in this test is part of the customers who take financing at BSI KC Meulaboh Imam Bonjol with a sample of customers who take financing with mudharabah contracts. The data analysis used was observation and interviews with Mr. Hidayat as BOSM and employees of BSI KC Meulaboh Imam Bonjol. The result of this research is that the implementation of working capital financing with Mudharabah contract has implemented the rules well compared to the creed of the National Sharia Council Fatwa number: 07/DSN-MUI/IV/2000.Keywords: Mudharabah, Working capital, Financing